THE IMPACT OF ENGLISH LANGUAGE PROFICIENCY ON THE RECRUITMENT AND SELECTION PROCESS: A STUDY FROM P.T. ENGLISH EFFICIENT SERVICES - Zenyka Viedeyona Zebedeus; Ronny Buha Sihotang (Universitas Islam Bandung, 2015)
The purpose of this research is to know the impact of English Language Proficiency (ELP) on the recruitment process and selection process. This research was conducted using the descriptive method, in which data was obtained by collecting and then analyzing to present a description about the research object. The collected data was analyzed using a linear regression analysis, Pearson Product Moment correlation coefficient analysis, significance test, and coefficient of determination analysis in order to obtain a conclusion. Data collection techniques include sending out validated questionnaires and interviewing the human resources manager of the company. Based on the linear regression and Pearson Product Moment statistical analysis, it was found that English Language Proficiency has a positive impact on both recruitment and selection. Based on the significance test, it was found that for recruitment, tcount = 1.013 < ttable = 1.960, which means that ELP does not have a significant impact on the recruitment process. For selection, however, the tcount = 3.162 > ttable value of 1.960, which means that ELP does have a significant impact on the selection process. Based on the coefficient of determination analysis, ELP affects the recruitment process as much as 3%. ELP affects the selection process as much as 23%.